Mythologeme of the Suffering God in Vyacheslav Ivanov’s Translation of Aeschylus’ Oresteia - Liia L. Ermakova (Studia Litterarum)
Vyacheslav Ivanov developed a mythologeme of the suffering god in Hellenic Religion of the Suffering God and Dionysus and Predionysianism; this mythologeme is at the core of his Dionysian concept. The essay argues that it also influenced his translations of tragedies by Aeschylus. The essay mainly deals with the translation of Ivanov’s trilogy “Oresteia”; Ivanov interprets the characters and the plot of the trilogy in the context of Dionysism. Lexical and semantic field of the mythologeme of the suffering god includes such lexemes as “strastoterpets” (“passion-bearer”), “strastnoj” (“of passion”), and a phrase “litso zemli” (“the face of the earth”) which have Christian connotations and repeatedly occur in the above-mentioned works by Ivanov. The article demonstrates that the same words are found in his Russian translation of “Oresteia.” In most cases, the translator has to add these words since they do not correspond to any particular words in the Greek original. The synthesis of Hellenic and Christian material, so important for Ivanov’s Dionysian concept, manifests itself at the linguistic level in his translation of “Oresteia.”